(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The theoretically most important perspective of the psychological study of human sexuality lies in the possibility of significant progress in solving the problem of specific mechanisms for integrating the biological and the social in man. According to K. Marx, hunger quenched with a knife and fork is no longer the same hunger that is quenched with fangs and claws.